Patients with COVID-19 Critical Illness Have a Significantly Higher Systemic Immune-Inflammatory Index on Admission - Fenty Fenty; Dita Maria Virginia; I Made Adi Ananda Putra; Devie Kristiani; Lisa Kuniasari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
The severity of Coronavirus Disease-2019 (COVID-19) has been correlated to the massive inflammatory response. Patients with COVID-19 have a higher inflammatory marker. The Systemic Immune-Inflammation Index (SII) can be considered as an indicator of the immune-inflammatory status. Many studies stated that SII could significantly indicate the severity of COVID-19. This research aimed to explore the admission SII score and its association with the severity of hospitalized patients with COVID-19. It was a cross-sectional observational study. Data were collected retrospectively from the electronic medical records (ERM) and Laboratory Information System (LIS).  The severity of COVID-19 and laboratory data on admission were analyzed. There were 180 patients (49.4% males and 50.6% female) with COVID-19 included in this research. Of these 180 patients, 22. 8% were categorized as mild, 18.9 moderate, 37.2% severe, and 21.1% were critical cases. Patients with critical illness had significantly higher SII scores than other groups with a p-value 0.05. SII on admission could be a noticeable predictor of the occurrence of critically ill COVID-19 patients.